Biomimicking tendon by electrospinning tissue‐derived decellularized extracellular matrix for tendon tissue engineering. Issue 4 (17th November 2022) - Ruhela, Aakanksha; Bhatt, Akshay; Rath, Subha Narayan; Sharma, Chandra Shekhar
Abstract: Tendon injuries disturb the equilibrium between mobility and stability, resulting in impaired functions and disabilities. Clinically, it is still challenging to regenerate fully functional tendons. Here, by direct electrospinning, we fabricate goat tendon‐derived extracellular matrix (tdECM) fibers using polycaprolactone (PCL) as a supporting polymer. We observe that the incorporation of tdECM particles strongly influences the characteristics of the scaffold, such as wettability, water uptake ability, and mechanical properties. The contact angle of the PCL/tdECM scaffold decreases to zero as compared to 122° for only PCL, making the scaffold completely hydrophilic. The water uptake ability increases by 200% by adding tdECM. The Physicochemical properties are evaluated using Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Electrospun fibers mimic the natural ECM structure, while tdECM can provide biochemical cues for the human mesenchymal stem cells to adhere to and differentiate. The scaffolds positively influence cell survival, proliferation, and alignment along the scaffolds of the human umbilical cord‐derived mesenchymal stem cells (hUMSCs). This study demonstrates the potential of electrospun ECM/polymer as a bioactive scaffold for in situ tendon regeneration. Abstract : A bioactive fibrous scaffold is developed by electrospinning goat tendon dECM with PCL. The prepared scaffold mimics the natural tendon tissue and will provide the necessary biochemical cues for stem cell growth and differentiation to form neo‐tendon tissue. This study clearly shows the potential of the fabricated bioscaffold as a bioactive scaffold for in situ tendon regeneration.